The Routledge handbook of the history of Moscow
1 online resource
Keywords: This timely handbook of recent scholarship on Moscow moves beyond today's headlines to present a broad spectrum of methodological and historiographic perspectives on the city's historical and contemporary significance.In the over 30 years since the dissolution of the Soviet Union, the history of Moscow has been explored through focused approaches including academic and architectural histories, guidebooks, fiction, and other texts. However, the broader history of Moscow as a whole has been a secondary consideration, and the lack of a unified body of academic works is profound. The Routledge Handbook of the History of Moscow redresses this deficiency by placing the city within its deserved longue dure??e context. It is particularly notable in that it includes chapters from historians who continue to work within the Russian Federation despite personal risk, scholars in the Russian diaspora, and Russian studies specialists from Europe, Canada, and the United States. Through this variety of lenses, readers will be provided with an understanding of Moscow's prominent role on the world stage, both past and present.The Routledge Handbook of the History of Moscow will be useful for university faculty seeking a non-textbook option for their undergraduate and graduate courses in Russian, Soviet, and post-Soviet studies.